Memahami Transformasi Kehidupan Rohani Para Suster Rubiah Pasionis-Malang Melalui Katekese Liturgis - Y. Wilson Bei Lena Meo; Hermanus Ndode; Yosef Usman (Sepakat : Jurnal Pastoral Kateketik, 2023)
This paper examines the transformation of the spiritual life of the Rubiah Pasionis-Malang sisters through the practice of liturgical catechesis, highlighting their contribution and role in the life of the Catholic church. A qualitative approach was used with a focus on spiritual experiences and daily changes influenced by liturgical catechesis. Data were collected through in-depth interview (April 25-28, 2024), highlighting the role of liturgical catechesis in shaping spiritual perceptions, values and actions. The purpose of this study was to deepen the understanding of the influence of liturgical catechesis on the transformation of the spiritual life of the Rubiah Pasionis and its relationship with their contemplative life in the Catholic church. The findings show that liturgical catechesis strengthens faith, deepens understanding of doctrine, and motivates engagement in spiritual practices. These findings are important in understanding the contribution of Rubiah Pasionis sisters in maintaining the spiritual life of the Catholic community they live in. This research also aims to explore the impact of liturgical catechesis on the transformation of Rubiah Pasionis' spiritual life, highlighting their vital role in the Catholic church. By highlighting the role of liturgical catechesis, this research provides insights into how Rubiahs enrich and deepen their spiritual experience in the church. By emphasizing a deep understanding of religious teachings, the Rubiahs are able to maintain their spiritual commitment in a simple and dedicated lifestyle. This gives a fuller picture of how liturgical catechesis not only affects the spiritual aspect, but also shapes daily behavior and attitudes towards life as a whole.